Analisis Pengaruh Parameter Terhadap MRR Pada Benda Kerja di Mesin CNC Turning dengan Metode Taguchi - Gilbran, Adin; Oktriadi, Yudi; Yudo, Eko (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
A high material removal rate is one of the goals to be achieved when machining parts with CNC turning. However, slow processing affects product processing time and increases production costs. To overcome this problem, it is necessary to set the correct process parameters so that they provide the most influential contribution to the MRR and produce maximum parameter values. This research aims to determine the influence of parameters (spindle speed, feed speed, and feed depth) on MRR and to determine the correct process parameter settings to produce maximum MRR, namely in this experimental design using an orthogonal array L9 (33) with three replications. The material used is ST-60 steel, with the data analyzed using the Taguchi Larger Is a Better method in analysis software. From the results of the mean factor calculation, the percent contribution to feeding was found to be 19.53%, while the depth of feeding was found to be 64.56%. The optimum MRR value is obtained from a combination of parameters in the CNC Turning process on ST-60 steel which can make the response value optimally obtained at the spindle speed 3,184 [rev/min], feeding 0.22 [mm/rev] and depth of cut 2.5 [mm].